Evaluation of the Sustainable Food Yard Program in Bengkulu City - Defri Yenti; Satria Putra Utama; Alia Azmi (AGRITROPICA : Journal of Agricultural Sciences, 2026)
The global food crisis has remained a serious issue since the 1970s, including in Indonesia, where food insecurity and malnutrition continue to pose challenges. To strengthen food security, the government introduced the Sustainable Food Yard Program (Pekarangan Pangan Lestari/P2L), which encourages households to utilize their yards to increase access to and availability of nutritious food. In Bengkulu City, the program has been implemented through Women Farmer Groups (Kelompok Wanita Tani/KWT) for the past 5 years. This study aims to describe the implementation of the P2L Program in Bengkulu City and analyze its effectiveness using a qualitative descriptive approach with the Logic Model framework. The findings show that the program has been implemented in accordance with technical guidelines and is supported by active KWT members, government funding, core activities such as nurseries and cultivation, adequate infrastructure, and assistance from relevant agencies.  The evaluation indicates that the P2L Program has been effective in the preparation and implementation stages, providing benefits such as increased knowledge and reduced household food expenditures among members. However, long-term sustainability has not been fully achieved due to the discontinuation of government funding, inappropriate targeting of locations and beneficiaries, and weak group dynamics. Therefore, local governments need to promote greater self-reliance by strengthening group institutions, improving access to capital and partnerships, refining targeting mechanisms, and enhancing continuous mentoring to ensure the program’s sustainability.